Influence of methadone on the anticonvulsant efficacy of valproate sodium gabapentin against maximal electroshock seizure in mice by regulation of brain MDA TNF-α - Moradi Jafari, Ali; Hassanpourezatti, Majid (Frontiers in Neurology, 2022)
Methadone is the most frequently used opioid therapy worldwide, with controversial effects on oxidative stress homeostasis. This study investigated the effects of intraperitoneal (i.p.) co-administration of methadone (0.1, 0.3, 1, and 3 mg/kg) and valproate sodium (300 mg/kg) or gabapentin (50 mg/kg) in the mice maximal electroshock (MES)-induced seizure model. The adverse effect of drugs was assessed using the chimney test. The levels of tumor necrosis factor-alpha (TNF-α) and malondialdehyde (MDA) contents were measured in mice brains after a single seizure. Administration of methadone alone resulted in a significant reduction in the duration of hind limb extension (HLE) than that in the control group. Methadone pretreatment at doses of 0.1 and 0.3 mg/kg i.p. decreased, and at doses of 1 and 3 mg/kg i.p. had an increasing effect on anticonvulsant efficacy of gabapentin. Pretreatment with all doses of methadone significantly decreased the valproate anticonvulsive efficacy. At doses of 1 and 3 mg/kg i.p. methadone per se increased brain MDA levels after MES-induced seizure. Administration of methadone (0.3 mg/kg i.p.) enhanced and at 3 mg/kg decreased gabapentin effect on brain MDA level, but their co-treatment did not lead to further increase in MDA. Methadone at 0.3–3 mg/kg enhanced the effect of sodium valproate on MDA levels in the brain, but at all doses significantly potentiated its effect on brain TNF-α levels. The drugs did not produce any side effects on motor coordination in experimental animals. In conclusion, methadone showed different effects on anticonvulsant actions of gabapentin and valproate through regulation of brain levels of MDA and TNF-α.